Investigation on crack problems of precast box culverts - Md. Yusof, Puteri Juieta Salwanni (2010)
Cracks of precast box culvert have arises due to improper quality of materials, incorrect specifications, faulty design, and mistakes in construction process or extreme environmental conditions. At the same time, external factors such as soil-water pressure, and soil movement, can contribute to the damage of these structures. The defects developed in any one particular component in a box culvert can extend and make weaken the box culvert to resist the loads. This study presents an investigation into the crack problems of 11 units precast box culvert elements. The investigation consists of tests which have been conducted to determine the causes of cracks and failure due to construction or design on the East Coast Highway Project Phase II – Bukit Besi to Bukit Payung. The methodology of this study have been carried out through a study of project documents, a site visit, and an analysis of the results of testing conducted upon the material used in the project. In this studies the nondestructive and destructive test were carried out to find the root causes of the problem in the culvert structures. As the results of investigation shows that the cracks of precast box culvert is due to constructions deficiencies such as overloading of backfilling, workmanship during manufacturing and not enough reinforcement as a design.